Online deviance in post-Soviet space: Victimisation, perceptions and social attitudes amongst young people, an Armenian case study - Tim Hall; Ulrike Ziemer (Digital Geography and Society)
This paper presents a survey-based case study of the experiences and perceptions of, and attitudes towards, various forms of online deviance amongst a largely female, educated sample of young people drawn predominantly from the Armenian capital city of Yerevan. It found high levels of reported victimisation and encounters with online deviance, including from multiple forms of online deviance. Online information that is deliberately misleading, biased or fabricated and information that is abusive or threatening, or that expresses a prejudice against a particular group were the two most widely reported categories of victimisation and encounter. The paper also explores the claim that forms of online deviance enjoy some degree of social legitimacy within post-Soviet space. Our case study found that online deviance enjoys very little social legitimacy amongst survey respondents. The case study explores the ways in which the experiences and perceptions of, and attitudes towards, various forms of online deviance vary across different forms of online deviance in a way that no studies have done previously. It also offers a rare empirical engagement with questions of online deviance within the post-Soviet space and the very first addressing online deviance in Armenia. This paper adds to our limited knowledge of the internal geographies of online deviance within post-Soviet space. The findings presented here begin to challenge the perception of post-Soviet countries, or countries in the post-Soviet space, as constituting a universal cyber-threat landscape and suggest that future research should probe the internal geographies of online deviance (and victimisation) across the region. It also highlights gender as a perspective from which future research might scrutinize online deviance. It further suggests nuanced policy stances more reflective of the empirical realities of different forms of online deviance across post-Soviet space.